The Church in Matthew - Martin, James P. (Interpretation, 1975)
On the whole, the church of Matthew is characterized more by the portrait of the disciple community provided in the Sermon on the Mount than by charismatic activity itself. Nevertheless, the center for Matthew is neither charismatic action nor ethical concern, but Jesus Christ.